Effect of Tillage Implements on Physiological Responses of Camel - Tiwari, G S; Verma, R N; Laddha, Vipin; Bhatt, Y C; Shrimali, H (Annals of Arid Zone, 2016)
Performance of five improved camel drawn implements namely MB plough. disc harrow, five-tyned cultivator. blade harrow and bund former were evaluated on farmers field in sandy soil. Draft requirement of tested .implements was found to be within the draft capacity of the camel. Effect of these implements on physiological responses of camels was also observed. The pulse rate. respiration rate. and rectal temperature increased with the duration of work and speed of camels was reduced in the similar conditions.